J. M. Davis, D. J. Hockney, W. K. Wilson (Editores) , Philosophical Logic, D. Reidel Publishing Company, Dordrecht-Holland, 1969, 277 pp - Moreno, Alberto (1973)
Fil: Moreno, Alberto. Pontificia Universidad Católica Argentina; Argentina